Florid xanthelasmata (yellow lids) in orbital Wegener's granulomatosis. Issue 5 (May 1995) - Tullo, A B; Durrington, P; Graham, E; Holt, L P; Easty, D L; Bonshek, R; Noble, J L
Abstract : AIMS--A new sign of florid xanthelasmata is described in four male patients with orbital manifestations of Wegener's granulomatosis. METHODS--The case notes of four patients with Wegener's granulomatosis, with orbital involvement accompanied by yellow lid lesions, are reviewed. RESULTS--All the patients had active Wegener's granulomatosis at the time the lid lesions were most florid. The lesions gradually resolved as the inflammatory disease was controlled with immunosuppressive agents. The lesions displayed marked asymmetry and predominantly involved the side with the most severe inflammation. Abnormalities of lipid metabolism were not identified and it is believed that the lesions developed in a susceptible anatomical region affected by a vasculitic process. CONCLUSION--A 'yellow lid' associated with orbital inflammation and is a strong pointer to the clinical diagnosis of Wegener's granulomatosis.